The Excited Electronic States Calculated for Cd1−xZnxS Quantum Dots Grown by the Sol-Gel Technique. (12th May 2010) - Sakly, A.; Safta, N.; Mejri, A.; Mejri, H.; Ben Lamine, A.
Abstract : The present paper is aimed to investigate theoretically the quantum confinement in Cd 1 − x Zn x S -related quantum dots with x the atomic fraction of Zn. For both electrons and holes, we have calculated the excited bound states with use of the spherical geometry model and assuming a finite potential at the boundary. For electrons, calculations were made by using Bessel function as an orthonormal basis. However, for holes, the confined subbands have been calculated based on squared quantum well envelope wave functions. The subband energies were evaluated for both electrons and holes versus zinc composition as well.